Atypical presentation of multiple myeloma: from heart failure to multiple myeloma - Sohaimi, Ainur Elliana; Jamhuri, Nur Syazwani; Ibrahim, Ismail (2024)
Multiple myeloma (MM) is a hematological malignancy commonly associated with bone pain, hypercalcemia, and renal failure. However, its presentation can occasionally mimic other medical conditions, which may delay diagnosis. This case report describes a patient who was initially diagnosed and treated for heart failure but was later found to have MM, highlighting the importance of considering MM in the differential diagnosis of heart failure.